Self-Instruction Techniques to Reduce Academic Procrastination among Indonesian University Students - Ratri, Prapti Madyo; Ruby, Arcivid Chorynia; Rahma, Min Yatul (Universitas Pahlawan Tuanku Tambusai, 2024)
Academic procrastination is the behavior of postponing completing academic assignments until the next time and replacing them with other enjoyable activities. This research aims to examine the success of self-instruction technique interventions in reducing academic procrastination experienced by students in Central Java. This research used a group one-group test experimental design. The data collection method uses a scale based on aspects of academic procrastination proposed by Steel (2007), namely Perceived time, Intention-action gap, Emotional distress and Perce, and ability. The subjects in this research were twenty students who showed high academic procrastination behavior based on the academic procrastination scale. The collected data were then analyzed using a parametric test with the T-test technique. The analysis results showed a significance value of 0.000 (p<0.05) which means that there was a decrease in academic procrastination behavior after being given an instruction technique intervention. So it can be concluded that the self-instruction technique is effective in reducing the level of student academic procrastination.